Recent Changes in Regulatory Development of Interreligious Marriage and Children’s Rights Based on Justice Perspective in Indonesia - Setiyowati (International Journal of Criminology and Sociology, 2021)
The issue of this study is the marriage registration with or on the basis of a court decision as referred to in Law Number 24 of 2013 concerning Population Administration is valid according to Law No. 1 of 1974 regarding Marriage. The Marriage Law is also one of the bases for the formation of the Population Administration Law. Bearing in mind that the Population Administration Act does not regulate further about how the procedure of marriage between people of different religions occur so that the terms and procedures and prohibition of marriage in the Marriage Law remain in force. Based on the above background, problems can be formulated to analyze marital regulations in the Marriage Law not yet fully based on the value of justice and its reconstruction. The findings show that the Reconstruction of marriage regulations in the perspective of the Marriage Law based on justice values can be carried out by reconstructing the provisions of articles governing the validity of marriages, which in their implementation or in their application do not indicate or provide a sense of justice for some people who will carry out marriages, particularly those related to the practice of interfaith marriages.